2022
DOI: 10.1155/2022/6452538
|View full text |Cite
|
Sign up to set email alerts
|

Stress Cone Effect Analysis and Optimum Design of Extra High-Voltage Cable Joint Using Neural Networks

Abstract: The major problem in high-voltage cable accessories is the electric field stress caused by the high-voltage level at the cable junction. In this paper, a neural network and simulation-based optimal design for extra high-voltage (EHV) cable accessory is proposed to ensure the optimum electrical design. The different kinds of geometries of the EHV underground cable accessory are realized in the Comsol Multiphysics software program, and the electric field analyses are conducted based on the finite element method.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…5 Thus, there is a huge demand for cable joints in long-distance cable systems. 6,7 Investigations into cable operation failure have revealed that the breakdown often occurs at the interface of cable accessories due to its complex multilayer insulation coordination issues (as shown in Figure 1b,c), which makes the cable accessory become the weakest link in the entire power cable system. [8][9][10] Hence, it is imperative to investigate the mechanism of the interfacial failure of the cable accessories, which is of great significance for reducing the number of cable system failures and ensuring the stability of the power system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Thus, there is a huge demand for cable joints in long-distance cable systems. 6,7 Investigations into cable operation failure have revealed that the breakdown often occurs at the interface of cable accessories due to its complex multilayer insulation coordination issues (as shown in Figure 1b,c), which makes the cable accessory become the weakest link in the entire power cable system. [8][9][10] Hence, it is imperative to investigate the mechanism of the interfacial failure of the cable accessories, which is of great significance for reducing the number of cable system failures and ensuring the stability of the power system.…”
Section: Introductionmentioning
confidence: 99%
“…Cable accessories, namely joints and terminals, as shown in Figure 1a, are indispensable components for power cable system to connect the different cable bodies 5 . Thus, there is a huge demand for cable joints in long‐distance cable systems 6,7 . Investigations into cable operation failure have revealed that the breakdown often occurs at the interface of cable accessories due to its complex multilayer insulation coordination issues (as shown in Figure 1b,c), which makes the cable accessory become the weakest link in the entire power cable system 8–10 .…”
Section: Introductionmentioning
confidence: 99%